Implementation of a Vacuum Sealer to Improve the Quality and Quantity of Neng Nana's UMKM - Didik Dwi Prasetya; Siti Sendari; Muhammad Ashar; Moh. Zainul Falah; Sujito Sujito; Wahyu Tri Handoko (Institute of Computer Science (IOCS), 2023)
In this modern era, frozen food is increasingly popular for consumption by the public. Not only for personal consumption, but also for the needs of food businesses such as restaurants, cafes or catering. The need for frozen food is growing, especially as more people choose to store food for longer periods of time. However, when frozen food is stored improperly, it can cause the quality of the food to decrease and even affect the health of consumers. Therefore, food businesses need to consider the right way to store frozen food. UMKM Neng Nana is engaged in Frozen Food with several products of instant baso aci, aroma roll sticks, mini spring rolls, baso aci seblak, melted bananas etc. UMKM Neng Nana is located in Housing Ardimulyo Kav. H no 4 Singosari Kab. Poor. In the packaging process for products, partners are still packaging using ordinary plastic, and have not been packaged using airtight packaging. As a food that is classified as semi-moist food, Mitra's products are foods that deteriorate quickly. The packaging at UMKM Neng Nana is still relatively conventional because they only use ordinary sealers, while their processed products come from semi-wet ingredients which require more effort to keep the products fresh. Vacuum sealers are a very important tool for frozen food businesses. In the frozen food business, food hygiene and quality must always be maintained.